Congo Red, an Amyloid-Inhibiting Compound, Alleviates Various Types of Cellular Dysfunction Triggered by Mutant Protein Kinase Cγ That Causes Spinocerebellar Ataxia Type 14 (SCA14) by Inhibiting Oligomerization and Aggregation - Takahiro Seki; Hideyuki Takahashi; Kazuhiro Yamamoto; Kota Ogawa; Tomoya Onji; Naoko Adachi; Shigeru Tanaka; Izumi Hide; Naoaki Saito; Norio Sakai (Elsevier, 2010)
Several missense mutations in the protein kinase Cγ (γPKC) gene have been found to cause spinocerebellar ataxia type 14 (SCA14), an autosomal dominant neurodegenerative disease. We previously demonstrated that the mutant γPKC found in SCA14 is susceptible to aggregation that induces apoptotic cell death. Congo red is widely used as a histological dye for amyloid detection. Recent evidence has revealed that Congo red has the property to inhibit amyloid oligomers and fibril formation of misfolded proteins. In the present study, we examine whether Congo red inhibits aggregate formation and cytotoxicity of mutant γPKC. Congo red likely inhibits aggregate formation of mutant γPKC - green fluorescent protein (GFP) without affecting its expression level in SH-SY5Y cells. Congo red counteracts the insolubilization of recombinant mutant γPKC, suggesting that the dye inhibits aggregation of mutant γPKC by a direct mechanism. Congo red also inhibits aggregation and oligomerization of mutant γPKC-GFP in primary cultured cerebellar Purkinje cells. Moreover, the dye reverses the improper development of dendrites and inhibits apoptotic cell death in Purkinje cells that express mutant γPKC-GFP. These results indicate that amyloid-inhibiting compounds like Congo red may be novel therapeutics for SCA14.[Supplementary Figures: available only at http://dx.doi.org/10.1254/jphs.10170FP] Keywords:: spinocerebellar ataxia type 14 (SCA14), protein kinase Cγ (γPKC), Congo red, aggregation, cerebellar Purkinje cell